Immune system dysregulation in the pathogenesis of non-alcoholic steatohepatitis: unveiling the critical role of T and B lymphocytes - Cebi, Merve; Yilmaz, Yusuf (Frontiers in Immunology, 2024)
Non-alcoholic fatty liver disease (NAFLD), characterized by the excessive accumulation of fat within the cytoplasm of hepatocytes (exceeding 5% of liver weight) in individuals without significant alcohol consumption, has rapidly evolved into a pressing global health issue, affecting approximately 25% of the world population. This condition, closely associated with obesity, type 2 diabetes, and the metabolic syndrome, encompasses a spectrum of liver disorders ranging from simple steatosis without inflammation to non-alcoholic steatohepatitis (NASH) and cirrhotic liver disease. Recent research has illuminated the complex interplay between metabolic and immune responses in the pathogenesis of NASH, underscoring the critical role played by T and B lymphocytes. These immune cells not only contribute to necroinflammatory changes in hepatic lobules but may also drive the onset and progression of liver fibrosis. This narrative review aims to provide a comprehensive exploration of the effector mechanisms employed by T cells, B cells, and their respective subpopulations in the pathogenesis of NASH. Understanding the immunological complexity of NASH holds profound implications for the development of targeted immunotherapeutic strategies to combat this increasingly prevalent and burdensome metabolic liver disease.